Education for Sustainable Development (ESD) Infusion into Curricula: Influences on Students' Understandings of Sustainable Development and ESD - Therese Ferguson; Carmel Roofe; Loraine D. Cook; Sharon Bramwell-Lalor; Carol Hordatt Gentles (Brock University, 2022)
Formal education for sustainable development (ESD) is in large part dependent on capacity-building and training of teachers as they are the individuals who must both deliver ESD at the classroom level as well as utilise their own knowledge, values and skills in support of sustainability. In this research, teacher educators within a higher education institution in Jamaica undertook a collaborative action research project to infuse ESD into their selected undergraduate and postgraduate courses during the spring semester of the 2018/19 academic year. Data were collected from approximately 140 students through the use of a pre- and post-infusion concept map, which sought to ascertain various facets including students' level of awareness and perspectives on sustainable development and ESD. Preliminary findings indicate that students' understanding of sustainable development broadened after the courses, with most students believing that sustainable development involves social, economic and environmental improvements that do not come at the expense of our natural resources. Additionally, students' thoughts about ESD shifted, with students highlighting aspects of the interdisciplinary nature of ESD and ESD as involving equitable and inclusive education, as well as attitudinal and behavioural changes. The findings of this research are significant in highlighting how the intentional infusion of ESD into courses across various specialisations can enhance students' knowledge and awareness of sustainable development and ESD.